2010
DOI: 10.1021/ja910843d
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Mediated Effect on Ion Channels Induced by the Anesthetic Drug Ketamine

Abstract: Anesthetic drugs have been in use for over 160 years in surgery, but their mode of action remains largely unresolved. We have studied the effect of (R)-(-)-ketamine on the biophysical properties of lipid model membranes composed of palmitoyloleoylphosphatidylcholine by a combination of X-ray diffraction and all-atom molecular dynamics simulations. In agreement with several previous studies, we do not find significant changes to the membrane thickness and lateral area per lipid up to 8 mol % ketamine content. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 71 publications
10
57
0
1
Order By: Relevance
“…In this way, they activate membrane receptors that in turn initiate a signaling pathway (Escriba 2006). Interestingly, the idea of lipid therapy is similar in spirit to the recent idea discussed by Cantor for the mechanism of general anesthetics (Cantor 1997;Jerabek et al 2010). He proposed that anesthetic molecules could play a role in the activation of membrane proteins by changing the pressure profile of a lipid membrane.…”
Section: Lipid Simulationsmentioning
confidence: 95%
“…In this way, they activate membrane receptors that in turn initiate a signaling pathway (Escriba 2006). Interestingly, the idea of lipid therapy is similar in spirit to the recent idea discussed by Cantor for the mechanism of general anesthetics (Cantor 1997;Jerabek et al 2010). He proposed that anesthetic molecules could play a role in the activation of membrane proteins by changing the pressure profile of a lipid membrane.…”
Section: Lipid Simulationsmentioning
confidence: 95%
“…during the formation of protein complexes; compare section 3.4), and (iii) expected changes in the lateral pressure profile of membranes may influence negatively the function of embedded membrane proteins (e.g. the opening and closing probability of membrane pores can get altered (Jerebek et al, 2010)). …”
Section: Scenarios For the Interaction Of Fullerenes With The Lipid Mmentioning
confidence: 99%
“…In this context, even when the argument for a lipid site action might be revived based on recent developments and research, 9 almost a century ago Meyer and Overton 10, 11 associated the potency of anesthetics with their solubility in a lipid bilayer, at a time in which the lipid bilayer structure had not even been described. It has been suggested that the solubility of anaesthetics in a lipid bilayer may cause a disturbance in membrane fluidity [12][13][14][15][16][17] that could affect the protein structure of sodium channel formation, and as a consequence of this perturbance, a conformational change in the ion channel could take place, resulting in the blockage of ion transduction.…”
Section: Introductionmentioning
confidence: 99%